(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: The purpose of this study is to review the correlation of spontaneous cerebrospinal fluid rhinorrhoea (CSFR) and Body Mass Index (BMI) and describe the demographics, the surgical techniques and outcomes. Materials and methods: We performed a retrospective review of clinical data of twenty patients diagnosed with spontaneous CSFR and treated at the Malaysian National University Medical Centre from 1997 to 2015. Result and Discussion: A total of 20 patients were selected in this research (19 females,1male). The mean age was 45.5 years with nineteen females and one male patient. The mean BMI was 33.1kg/m2.Majority of patients with spontaneous leaks are females in their forties. The bath plug technique, onlay of middle turbinate grafts, nasoseptal flaps and mucoperiosteal grafts techniques were used and three patients reported recurrences. Conclusion: Spontaneous CSFR is more common in women in their 40s with BMI>25. The most common sites of leaks are the cribriform plate followed by the sphenoid sinus. Spontaneous CSFR cases are strongly related with increased BMI. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.322-328